Bubble Tree Drawing Algorithm - Grivet, Sébastien; Auber, David; Domenger, Jean-Philippe; Melançon, Guy (ICCVG'04: Proceedings of the International Conference on Computer Vision and Graphics, 2004)
In this paper, we present an algorithm, called Bubble Tree, for the drawing of general rooted trees. A large variety of algorithms already exists in this field. However, the goal of this algorithm is to obtain a better drawing which makes a trade off between the angular resolution and the length of the edges. We show that the Bubble Tree drawing algorithm provides a planar drawing with at most one bend per edge in linear running time.